Evaluation of Clinical Learning for Undergraduate Midwifery Students and Professional Midwifery Students - Nuli Nuryanti Zulala; Siti Istiyati; Esitra Herfanda (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Exposure to clinical settings reinforces theoretical instruction acquired in the classroom and provides students with authentic professional situations. Through engagement in these clinical activities, midwifery students are encouraged to acquire knowledge through direct involvement by gathering relevant information, conducting analyses, and applying appropriate management strategies for clients encountered during practice. Therefore, a systematic assessment of the clinical learning environment and the instructor’s role is essential for creating a supportive and constructive educational atmosphere. Consequently, the objective of this study is to evaluate the clinical learning practices experienced by undergraduate midwifery students and those enrolled in professional midwifery programs. Method: A total of 159 respondents, consisting of undergraduate midwifery students and professional midwifery education students in the even semester of the 2024/2025 academic year, participated in this survey. Data collection utilized the CLEQ 2.0 instrument, which had previously been translated into Indonesian using the forward-backward translation procedure and had been tested for validity and reliability. This instrument was used to measure several aspects, including case availability, learning motivation, supervisory guidance, and relational interactions between clients and midwives. Result: Analysis of the measurement results showed that the lowest average score was recorded on item number four with an average value of 3.42, while the highest average score was found on item number ten with a value of 4.38. The overall mean score was 4.10. Conclusion: The implementation of clinical learning for undergraduate midwifery students and professional midwives yielded satisfactory results.